Achieving Highly Reversible Zinc Anodes via N, N‐Dimethylacetamide Enabled Zn‐Ion Solvation Regulation. Issue 27 (6th June 2022) - Wu, Fangfang; Chen, Yuchao; Chen, Yulong; Yin, Ruilian; Feng, Yancong; Zheng, Dong; Xu, Xilian; Shi, Wenhui; Liu, Wenxian; Cao, Xiehong
Abstract: Although aqueous zinc–ion batteries (ZIBs) are promising for scalable energy storage application, the actual performance of ZIBs is hampered by the irreversibility. Optimization of electrolyte composition is a relatively practical and facile way to improve coulombic efficiency (CE) and Zn plating/stripping reversibility of ZIBs. N, N ‐Dimethylacetamide (DMA) has a higher Gutmann donor number (DN) than that of H2 O, abundant polar groups, and economic price. Herein, a mixture electrolyte containing 10 vol% DMA and ZnSO4, which has an enhanced Zn reversibility almost fourfold higher than that of pure ZnSO4 electrolyte, is demonstrated. The density functional theory (DFT) calculation and spectroscopic analysis reveal DMA has the ability to reconstruct the solvation structure of Zn 2+ and capture free water molecules via forming Hbonds. The inhibited dendrite growth on Zn anode is further clarified by an in situ characterization. This work provides a feasible way for the development of long‐lifespan ZIBs. Abstract : An electrolyte with potential practical value is developed for highly reversible Zn anode and long‐lifespan zinc–ion batteries using an additive of N, N ‐dimethylacetamide (DMA), which has an ionic conductivity close to that of aqueous ZnSO4 electrolyte and economic price. The essential role of DMA in regulating the solvation shell of Zn 2+, suppressing side reactions, and guiding to a uniform deposition of Zn is also revealed.